Experimental investigation of thin-walled structural steel members and connections - Chiew, Sing Ping. (2008)
Thin-walled structural steel members and connections are being used increasingly because of its favourable strength-to-weight ratio, versatile sectional configurations and ease of erection for structural applications. The purpose of this report is to present four (4) main areas of experimental investigation involving such members and connections, namely: 1. Thin-walled steel channels with complex stiffeners subject to pure axial compression. 2. Thin-walled Z-sections with simple and complex stiffeners subject to major axis bending. 3. Thin-walled stainless steel rectangular hollow sections subject to compression. 4. Thin-walled overlapped K-Joints subject to chord face failure.